MENGKOMBINASIKAN METODE BELAJAR MAHASISWA AKTIF DAN METODE KASUS DALAM PEMBELAJARAN AKUNTANSI DAN MANAJEMEN - Priyawan, Sunu (Program Doktor Ilmu Ekonomi, 2009)
Abstract. This Article do not have an eye to to fight against two teaching and learning method which[is generally used in learning in college: tutorial method with case study method. This article aim to to lay open growth of method which forming college grad attitude, management of case with case method, case report format and content, and also presentation of case verbally. This article is enclosed with subject matter syllabus example of using method combination of tutorial and case study method, case example, and case report example.Â Keyword: Â Study, method learn.